Monitoramento da restauração ecológica em matas ciliares do bioma Pampa - Procknow, Djoney (2023)
The Pampa biome has a lack of research in the ecological restoration field, especially in monitoring strategies. The applied nucleation aims to accelerate the restoration process in degraded areas. Just implementing the strategies is not enough, it is necessary to verify that the objectives are being met through periodic evaluations in the monitoring stage. The general objective of the present study is to evaluate, through ecological indicators, the progression of ecological restoration by applied nucleation in a Permanent Preservation Area of riparian forest in the Pampa biome, southern Brazil. This thesis is structured in chapters format. In chapter 1, ecological indicators of composition (richness, abundance and diversity), structure (leaf litter depth, canopy cover, soil cover and nucleus area) and function (dispersion syndrome) were evaluated over time to verify the applied nucleation progression. Dendrometric variables (height, diameter at the breast height, nucleus area and crown area) were measured to evaluate the development of trees planted in the nuclei. The assessments occurred in two areas, one under active restoration by applied nucleation and the other one under passive restoration. The areas showed differences in floristic composition, dendrometric variables and ecological indicators between the monitorings. The ecological indicators of structure (canopy cover, soil cover by litter and by trees) and function (biotic dispersion syndrome) were statistically higher in the second monitoring in the area under active restoration. In the area under passive restoration, the indicators of structure (leaf litter depth and soil cover by litter and trees) and function (biotic dispersion syndrome) were also statistically higher in the second monitoring. The objective of chapter 2 was to evaluate, through ecological indicators (idem to chapter 1), after ten years of implantation, the effectiveness of the applied nucleation. As with Chapter 1, the assessment was carried out in two areas. In the area under applied nucleation, the plots were evaluated in intra-nuclei (inside the nuclei) and inter-nuclei (outside the nuclei). There was a significant difference between passive restoration, intra-nuclei and inter-nuclei for the evaluated indicators. The highest averages were to intra-nuclei, followed by inter-nuclei and passive restoration. The results provide in this thesis demonstrate that applied nucleation is effective for restoration in the study area. The nuclei are in full development, helping the successional trajectory and accelerating the restoration. The area under passive restoration is in the initial process of ecological succession, however, it presents evidence of modifications. Monitoring over time is recommended in order to have a better understanding of the dynamics of ecological succession in restorative areas in the Pampa biome.